The role of small business in the national economy: world experience and domestic practice - E. E. Frolova; M. Kh. Tsoloev (Путеводитель предпринимателя)
The article discusses the role of small business in Russia and abroad, also highlights the problems that affect SMEs, the situation with the coronavirus pandemic, which affected Russian entrepreneurs.